Dynamic Multilingual Identities: A linguistic ethnography exploring identity, multilingualism and language policy in primary school aged, migrant learners and their families in Ireland. - Whittaker, Chelsea Ann (Trinity College Dublin. School of Education. Discipline of Education, 2024)
Previously a country with a sustained history of emigration, Ireland has experienced significant immigration in the last thirty years, which has resulted in an increasingly diverse ethnolinguistic landscape (Central Statistics Office, 2016; Devine, 2005; O'Connor et al., 2017). Now, Ireland must seriously consider diversity, language and education policy issues (Lin & Martin, 2005). In particular, this diversity has presented challenges in supporting multilingual learners in Irish schools (Central Statistics Office, 2022; Faas et al., 2018; Nowlan, 2008). Migration may impact on one's sense of self, demanding internal reflection and reassessment of linguistic and identity choices, which can result in fragmented identities, multilingual dynamic identities and new formations of identity emerging (Hewings, 2012; O'Connor et al., 2017; Rassool, 2012). Language learning can be emancipatory; however migrant families must constantly navigate linguistic issues, such as deciding which languages to use in which contexts, which languages to maintain and which languages to learn (Hirsch & Lee, 2018). Furthermore, migrant caregivers are often faced with a linguistic reality in which minority or heritage languages are spoken in the home and dominant, majority languages are spoken in the wider community (Schwartz, 2010). This research investigated how the language practices, proficiencies and ideologies of multilingual migrant learners attending English-medium primary schools are shaped within home and school environments. This research involved intensive engagement with two multilingual, migrant families. The research focused on homework as a transitional space in which family and school language policies interact. Data were generated using observations, interviews and document analysis. Reflexive Thematic Analysis (Braun & Clarke, 2013, 2022) was employed to generate themes from the data. Evidence demonstrated disjunctures between official language-in-education policy, classroom practice and the experiences of the participating learners (Dillon, 2016; Hornberger, 2006; Ricento 2000, 2009). Furthermore, learners employed their own agency to navigate differences in linguistic environments, particularly between the school and home, and in so doing establishing dynamic, multilingual identities (Curdt-Christiansen, 2018; Smith-Christmas, 2021). Where disjunctures were present, the homework space was a particular interaction in which such tensions were evident, affecting the interaction between learners, caregivers and homework tasks. This thesis provides relevant examples of how learners' experiences of integration and language learning may impact on their identity development as dynamic, multilingual individuals in Ireland. This research also contributes to both broader social and migration policy research in Ireland considering recent unrest, and multilingualism and language policy research, by providing a sociolinguistic perspective on how migrant, heritage language speakers' linguistic identities are developing in 21st century Ireland.
APPROVED